Efficacy of 25% dextrose versus breast milk on pain and duration of cry during heel prick in neonates: A systematic review and meta-analysis - Sabitri Acharya; Pity Koul; Santosh Pokhrel; Talagatoti David Ratna Paul (Journal of Integrative Nursing)
Neonates, especially admitted to neonatal intensive care unit, frequently need various medical interventions in their early days. A common procedure is the heel prick for blood sampling. Although necessary for diagnosis, this procedure can be stressful for neonates, causing pain, extended crying, and discomfort. Reducing distress in neonates during such procedures is important for the well-being of neonates and the satisfaction of caregivers and healthcare providers. Therefore, this review aims to identify and compare the efficacy of 25% dextrose and breast milk on pain and duration of cry among neonates during heel-lance. As part of its review process, the article examined widely used databases, including PubMed, EMBASE, Cochrane, Academia, and Google Scholar. For the meta-analysis, the authors utilized RevMan 5.4. All eligible trials were analyzed using the Cochrane Risk of Bias Tool to assess the quality of the included studies and evaluate the risk of bias. Out of 131 studies reviewed, seven studies were included in meta-analysis of pain, and four studies were included in duration of cry. The results show that 25% dextrose is more effective to reduce pain among neonates during minor invasive procedure like heel prick (P < 0.00001), whereas both interventions are effective in the reduction of crying duration. This review highlights that dextrose is more effective in reducing pain in comparison to breast milk. However, additional well-designed studies with larger sample sizes and extended follow-up periods are needed to validate and build upon the current findings. Hence, this review underscores the importance of utilizing effective pain management strategies, such as 25% dextrose, to enhance neonatal care and improve the overall well-being of newborns during invasive procedures.